2010
DOI: 10.1038/sj.bjc.6605648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prostate cancer testing: an evaluation of the emotional consequences of a negative biopsy result

Abstract: BACKGROUND: When testing for prostate cancer, as many as 75% of men with a raised prostate-specific antigen (PSA) have a benign biopsy result. Little is known about the psychological effect of this result for these men. METHODS: In all, 330 men participating in the prostate testing for cancer and treatment (ProtecT) study were studied; aged 50 -69 years with a PSA level of X3 ng ml À1 and a negative biopsy result. Distress and negative mood were measured at four time-points: two during diagnostic testing and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 31 publications
5
67
0
1
Order By: Relevance
“…This was not suprising and also consistent with the literature. 3,16 An important finding of our study was the difference of effect of video-based education on patient anxiety post-information STAI-S scores between the 2 groups. While the post-information STAI-S scores remained stable in patients who received only written information (Group 2) (p = 0.89), there was a significant decrease of post-information STAI-S scores in patients who received both written and video education (Group 1) (p = 0.01).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This was not suprising and also consistent with the literature. 3,16 An important finding of our study was the difference of effect of video-based education on patient anxiety post-information STAI-S scores between the 2 groups. While the post-information STAI-S scores remained stable in patients who received only written information (Group 2) (p = 0.89), there was a significant decrease of post-information STAI-S scores in patients who received both written and video education (Group 1) (p = 0.01).…”
Section: Discussionmentioning
confidence: 90%
“…3 About 20% of men undergoing to prostate biopsy felt anxious and/or highly stressed prior to the biopsy. 16 Pain, evaluation for possible malignancy and rectal route used by the probe are some possible reasons of the anxiety. Providing a detailed description of the diagnostic method or surgical procedure is one way to reduce anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Zisman et al 43 found that undergoing a prostate biopsy can have an impact on the patient's well-being due to causing pain and anxiety. Macefield et al 44 reported that although most men coped well with undergoing a biopsy, a minority experienced elevated distress at the time of biopsy and after receiving a negative result. The authors stress that men should be informed of the risk of distress that is related to diagnostic uncertainty before consenting to PSA testing and possibly undergoing a biopsy.…”
Section: Shared Decision Makingmentioning
confidence: 99%
“…Psychologically, anxiety frequently co-occurs with biopsies and psa screening [19][20][21] . Macefield and collaborators 22 reported that approximately 20% of screened men experienced high levels of tension and anxiety at the time of biopsy, as well as clinically significant distress. Prostate-specific antigen tests were also positively associated with anger, depression, and confusion in a smaller proportion of men participating in pca screening 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Macefield and collaborators 22 reported that approximately 20% of screened men experienced high levels of tension and anxiety at the time of biopsy, as well as clinically significant distress. Prostate-specific antigen tests were also positively associated with anger, depression, and confusion in a smaller proportion of men participating in pca screening 22 . Considering that most patients with elevated psa and hgpin actually have benign conditions that will not progress to pca, there are reasons to believe that those patients might undergo unnecessary psychological distress as a result of screening.…”
Section: Introductionmentioning
confidence: 99%